PERENCANAAN PENDIDIKAN GURU DI SEKOLAH DASAR - Idawati; Nurul Pratiwi; Yulia; Nursafitri (STKIP Subang, 2025)
Basic education serves as a strategic foundation for character building, the strengthening of literacy and numeracy skills, and the social-emotional development of learners, positioning elementary school teachers as key actors in the success of the learning process. Improving the quality of basic education cannot be separated from systematic, well-directed, and sustainable educational planning for teachers. Such planning includes identifying needs, setting objectives, formulating strategies, and developing teacher competencies to respond to the dynamics of modern learning, particularly in the implementation of the Merdeka Curriculum, which requires mastery of differentiated instruction, formative assessment, technology integration, and project-based learning. Without careful planning, teachers’ professional development may become ineffective and have minimal impact on learning quality. Furthermore, the rapid advancement of science and technology demands that elementary school teachers possess adaptive pedagogical, professional, social, and personal competencies to address the diverse characteristics of learners. Therefore, teacher education planning grounded in philosophical, psychological, and juridical foundations is essential to ensure that teachers receive relevant training and mentoring, enabling them to create meaningful, inclusive, and holistic learning experiences.